Pengaruh Komitmen Organisasi, Perspektif Budaya Tri Hita Karana, Dan Whistleblowing System Dalam Pencegahan Fraud Pada Koperasi Simpan Pinjam Se Kabupaten Badung - Ni Putu Mariani; Putu Cita Ayu; Ni Putu Trisna Windika Pratiwi (UNHI Press, 2025)
Fraud according to the ACFE (Association of Certified Fraud Examiners) is an act of deception, deception, cunning, deception and other dishonest methods committed by a person or entity and can result in several unfavorable benefits to the individual or entity or other party. “The high intensity of cheating, deception and embezzlement practices that occur in a public institution with all its modes, from the simplest to the very sophisticated and complex, should make all parties aware of building a commitment to the implementation and good governance consistently and broadly at all levels of society. . This research aims to determine the influence of Organizational Commitment, Tri Hita Karana Cultural Perspective, and Whistleblowing System in Fraud Prevention in Badung Regency Savings and Loans Cooperatives. The population in this study was all employees of savings and loan cooperatives in Badung Regency, totaling 6,572 people. The number of samples in this study was 99 people, the research data was obtained through the results of distributing questionnaires and tested using multiple linear regression analysis techniques. The results of this research show that organizational commitment has a positive and significant effect on fraud prevention, Tri Hita Karana culture has a positive and significant effect on fraud prevention, and the Whistleblowing System has a positive and significant effect on fraud prevention. Looking at the research results, in the future the cooperative is expected to be able to increase the organizational commitment of employees so that they are able to be responsible and contribute to their work optimally”